2015
DOI: 10.1097/mcg.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in Chronic Hepatitis B Patients Treated With Tenofovir Disoproxil Fumarate or Entecavir Monotherapy

Abstract: TDF treatment was not an independent predictor for significant deterioration of renal function. Renal function of chronic hepatitis B patients on antiviral therapy should be monitored, especially in those who are older and/or with mildly impaired renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 20 publications
3
32
1
5
Order By: Relevance
“…As TDF was first approved by Chinese FDA just 2 years ago, very limited data can be obtained from the follow-up patients. Secondly, most results in this study showed good consistency with other studies around the world [2022, 24]; however, we can not be totally sure that TDF has the same effects for the Chinese population. Finally, total drug resistance measurements were not made in previous studies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As TDF was first approved by Chinese FDA just 2 years ago, very limited data can be obtained from the follow-up patients. Secondly, most results in this study showed good consistency with other studies around the world [2022, 24]; however, we can not be totally sure that TDF has the same effects for the Chinese population. Finally, total drug resistance measurements were not made in previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…Ha et al [24] also indicated that TDF is not an independent predictor of severe kidney damage; however, they proposed close monitoring of renal function during antiviral therapy, especially in the elders or patients with impaired renal function. In our study, we also monitored the renal function via serum inorganic phosphorus levels during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Sebbene negli studi clinici randomizzati, controllati, in pazienti selezionati con epatite cronica B, il trattamento con TDF si sia dimostrato ben tollerato e senza segnalazioni di tossicità renale clinicamente significativa, l'esperienza clinica real life ha riportato casi di compromissione della funzione renale fino all'insufficienza renale e alla sindrome di Fanconi [6,7,[10][11][12][13][14][15][16][17][18][19][32][33][34][35][36][37][38][39]. Spesso i fattori di rischio per un peggioramento della funzione renale sono l'età avanzata, l'ipertensione arteriosa e una preesistente riduzione del filtrato glomerulare.…”
Section: Discussioneunclassified
“…Tra i NUC approvati, entecavir (ETV) e tenofovir disoproxil fumarato (TDF) sono raccomandati in prima linea nel trattamento dell'epatite cronica B, poiché entrambi sono antivirali potenti e con elevata barriera alla resistenza [1][2][3]. Negli studi registrativi e negli studi clinici a lungo termine, sia ETV che TDF hanno mostrato un profilo di sicurezza favorevole [4][5][6][7][8][9][10][11], anche se recentemente sono stati segnalati nella pratica clinica eventi avversi a livello Efficacia e sicurezza di entecavir dopo switch da tenofovir per comparsa di effetti collaterali renali M. Viganò renale e osseo nei pazienti trattati per lungo tempo con TDF [6,7,[10][11][12][13][14][15][16][17][18][19]. I meccanismi alla base della potenziale tossicità dei NUC sono legati alla loro capacità di inibire la DNA polimerasi ϒ mitocondriale umana quando le concentrazioni intracellulari dei NUC superano una soglia critica [12].…”
Section: Introduzioneunclassified
“…Moreover, a Cockroft-Gault estimated CrCL ≥70 ml/min is an entry criterion for most clinical trials now available, limiting the experience in patients with established renal damage (23). In preliminary data of naïve patients treated with TDF or ETV, the risk of renal function worsening was similar in both groups; older age and impaired renal function before starting therapy were predictors of renal damage during treatment (28).…”
Section: Tenofovir and Renal Function In Clinical Trialsmentioning
confidence: 92%